2014
DOI: 10.1107/s1600536814004383
|View full text |Cite
|
Sign up to set email alerts
|

2-{2,4,6-Tris(bromomethyl)-3,5-bis[(1,3-dioxoisoindolin-2-yl)methyl]benzyl}isoindoline-1,3-dione toluene monosolvate

Abstract: Key indicators: single-crystal X-ray study; T = 100 K; mean (C-C) = 0.003 Å; R factor = 0.026; wR factor = 0.057; data-to-parameter ratio = 22.8.In the title compound, C 36 H 24 Br 3 N 3 O 6 ÁC 7 H 8 , the toluene solvent molecule is associated with the receptor molecule via C-HÁ Á Á bonding. The planes of the phthalimido groups are inclined at 77.0 (1), 63.0 (1) and 77.8 (1) with respect to the benzene ring. The molecular conformation is stabilized by C-HÁ Á ÁO and C-HÁ Á ÁBr hydrogen bonds. The crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Regarding the description of crystal structures of tri-to hexasubstituted benzene derivatives, the number of hits could be reduced to three relevant entries. This includes two hexasubstituted benzene derivatives consisting of three isoindoline-1,3-dione groups (phthalimidomethyl groups) and either methoxy (IDOBIO; Rosien et al, 2013) or bromomethyl groups (LOFBIT; Koch et al, 2014) in each of the 2-, 4-and 6-positions of the benzene ring. Furthermore, a 1,3,5-trisubstituted benzene derivative, namely 3,5-bis(phthalimidomethyl)phenyl-tert-butyldimethylsilyl ether (WIKRAK; Domínguez et al, 2007), has been found.…”
Section: Database Surveymentioning
confidence: 99%
“…Regarding the description of crystal structures of tri-to hexasubstituted benzene derivatives, the number of hits could be reduced to three relevant entries. This includes two hexasubstituted benzene derivatives consisting of three isoindoline-1,3-dione groups (phthalimidomethyl groups) and either methoxy (IDOBIO; Rosien et al, 2013) or bromomethyl groups (LOFBIT; Koch et al, 2014) in each of the 2-, 4-and 6-positions of the benzene ring. Furthermore, a 1,3,5-trisubstituted benzene derivative, namely 3,5-bis(phthalimidomethyl)phenyl-tert-butyldimethylsilyl ether (WIKRAK; Domínguez et al, 2007), has been found.…”
Section: Database Surveymentioning
confidence: 99%
“…Moreover, the Br1Á Á ÁCg(B) distance of 3.317 (2) Å and the well-defined bonding geometry [C9-Br1Á Á ÁCg(B) = 173.0 (1) ] indicate the presence of an intermolecular BrÁ Á Á halogen bond (Mazik et al, 2010a,b;Koch et al, 2017;Legon, 1999;Megrangolo & Resnati, 2008). The distance of 3.213 (2) Å between atom Br2 and amide atom O1A of an adjacent molecule [symmetry code: (A) x + 1, y À 1, z], which is considerably less than the sum of the van der Waals radii of the respective atoms (3.37 Å ), suggests the existence of an attractive BrÁ Á ÁO halogen bond (Politzer et al, 2007;Koch et al, 2014Koch et al, , 2015. One of the host molecules participates in offsetstacking [CgÁ Á ÁCg = 3.709 (2) Å ; symmetry code: Àx, Ày, Àz + 1].…”
Section: Figurementioning
confidence: 99%